Performance evaluation of relay node deployment in Long Term Evolution-Advanced (LTE-A) network / Muhammad Firdaus Sulaiman - Sulaiman, Muhammad Firdaus (2017)
The uses of wireless networks has progressively increased over the past years and it has become the most important medium communication and cost effieciently. With the rapid development of mobile communication, mobile telephone users are expecting higher network capacity and good connection quality especially at the cell-edges , were user experiencing bad signal coverage because of small cell capacity and cell coverage.